Experience of Implementing Moisture Sorption Control in Historical Archives - P. Zítek; T. Vyhlídal; J. Chyský (Acta Polytechnica, 2006)
This paper deals with a novel approach to inhibiting the harmful impact of moisture sorption in old art works and historical exhibits preserved in remote historic buildings that are in use as depositories or exhibition rooms for cultural heritage collections. It is a sequel to the previous work presented in [2], where the principle of moisture sorption stabilization was explained. Sorption isotherm investigations and EMC control implementation in historical buildings not provided with heating are the main concern in this paper. The proposed microclimate adjustment consists in leaving the interior temperature to run almost its spontaneous yearly cycle, while the air humidity is maintained in a specific relationship to the current interior temperature. The interior air humidity is modestly adjusted to protect historical exhibits and art works from harmful variations in the content of absorbed moisture, which would otherwise arise owing to the interior temperature drifts. Since direct measurements of moisture content are not feasible, the air humidity is controlled via a model-based principle. Two long-term implementations of the proposed microclimate control have already proved that it can permanently maintain a constant moisture content in the preserved exhibits.